Phenological, physicochemical, and productive characteristics of 'Venus' grapevine onto rootstocks - Tecchio, Marco Antonio [UNESP]; Rodrigues da Silva, Marlon Jocimar [UNESP]; Maia Paiva, Ana Paula [UNESP]; Moura, Mara Fernandes; Terra, Maurilo Monteiro; Paioli Pires, Erasmo Jose; Leonel, Sarita [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to evaluate the phenological characteristics and yield of 'Venus' grapevine (Vitis labrusca) grafted onto different rootstocks, as well the physicochemical traits of its grapes during the 2013, 2014. and 2015 crop seasons. The evaluated rootstocks were 'IAC 766', 'IAC 572', 'IAC 313' and 'IAC 571-6'. The length of the main phonological stages of the grapevine and its thermal demands were assessed during two growing seasons and expressed as days after pruning and degree-day sum, respectively. Grapevine yield and berry physicochemical characteristics were assessed during three crop seasons. 'Venus' phenological cycle and thermal demands, as well as the chemical characteristics of its grapes, varied with the climate conditions during the crop seasons. Low temperatures increased the grapevine cycle, and higher rainfall indices caused a decrease in the soluble solids of berries, as well as an increase in their titratable acidity. The 'IAC 766' and 'IAC 571-6' rootstocks promote a greater precocity to 'Venus' grapevines, and 'IAC 572' promotes a higher grapevine yield and better physicochemical characteristics of 'Venus' grapes.
Keywords: Vitis labrusca; degree-days; hybrid grapes; phenological stages; thermal requirement